A comprehensive review of summer savory (Satureja hortensis L.): promising ingredient for production of functional foods - Ejaz, Afaf; Waliat, Sadaf; Arshad, Muhammad Sajid; Khalid, Waseem; Khalid, Muhammad Zubair; Rasul Suleria, Hafiz Ansar; Luca, Marian-Ilie; Mironeasa, Costel; Batariuc, Ana; Ungureanu-Iuga, Mădălina; Coţovanu, Ionica; Mironeasa, Silvia (Frontiers in Pharmacology, 2023)
This review aims to measure the different aspects of summer savory including biological activity, medicinal properties, nutritional value, food application, health prospective and their usage as a feed additive in broilers. However, the herb-related toxicity is also overviewed. Summer savory leaves are abundant in total phenolic compounds (rosmarinic acid and flavonoids) that have an powerful antioxidant impact. The rosmarinic (𝛼-O-caffeoyl-3,4-dihydroxy-phenyl lactic) acid are identified in summer savory as a main component. According to phytochemical investigations, tannins, volatile oils, sterols, acids, gums, pyrocatechol, phenolic compounds, mucilage and pyrocatechol are the primary compounds of Satureja species. Summer savory extract shows considerable biological potential in antioxidant, cytotoxic, and antibacterial assays. Regarding antioxidant activity, the summer savory extract is display an inhibitory concentration for lipid peroxidation. Summer savory has also Fe (III) reductive and free radical scavenging properties. Summer savory is also contained minerals and vitamins. . Sammer savory has important biological properties including antimicrobial activity, antioxidant activity, protection Jurkat T Cells, Alzheimer's disease, cancer, anti-infection, cardiovascular diseases, antidiabetic and anti-cholesterol effects. The leaves and stems of this plant are employed in the food, feed and pharmacological industries due to their antioxidant properties and substantial nutritional contents. Conclusively, summer savory is strongly recommended for human health due to its versatile properties and medicinal use.